Frequency of Meningitis in Cases with a History of Getting the MMR Vaccine within the Past 45 Days - Sohaib Riaz, Isha Adeel Chaudhary, Abdullah Umer Rehan, Qurat-Ul-Ain Khalid, Ismat Tahira, Aneeqa Adnan, Muhammad Ahsan, (Pakistan Journal of Medical & Health Sciences, 2022)
To estimate the frequency of meningitis in cases having history of receiving the MMR vaccine in last 45 days. Methodology: This observational research evaluated 100 cases of meningitis in the final 45 days after MMR vaccination. All children admitted to Madinah Teaching Hospital's Paediatric unit were included. Duration of study was 12 months from Feb 2021 to March 2022. All 9-43-month-old male/female patients of any socioeconomic level and location were examined for meningitis. Meningitis was classified as a CSF WBC pleocytosis of 5/mm3. Clinical data was compiled using parents', patients', and hospital records' information. In addition to the normal CSF investigation, all frozen CSF samples were tested for enteroviruses (EV) and mumps using PCR (culture, cell count, sugar, and protein). Results: In our study, 57% of the cases were less than 24 months old, 43% were between 25 and 43 months old, 48% were male, and 52% were female. Meningitis incidence in patients with recent MMR vaccination was 5%. Conclusion: We observed 5% of meningitis cases (9-43 months) occur within 45 days after the initial MMR immunization. Keywords: Children, MMR Vaccine, meningitis